Investing in Human Capital in Tourism Companies - NOVOLODSKAYA, Galina Ivanovna; CHICHEROVA, Elena Yuryevna; PONKRATOVA, Liudmila Alekseevna; GRACHEVA, Nadezhda Alekseevna; ILKEVICH, Sergey Viktorovich (Journal of Environmental Management and Tourism, 2019)
This paper addresses investing in human capital in tourism companies. It is established that human capital is not a purely economic phenomenon but has a markedly pronounced social and public nature and is a socio-economic category for most tourism companies. Factoring in that human capital cannot self-reproduce, the authors make a case for the advisability of investing in human capital as a principal way to increase it. It is proven that in tourism companies human capital forms and develops as a result of the process of investing in their human potential, i.e . the human component is an object of investment – and, consequently, a source of a firm’s future revenue. The authors suggest that in today’s climate of an unstable economic environment it may be worth focusing further research on the mechanics of marketing of a tourism firm’s human capital.